Effects of silicon and manganese content on the oxidation behavior of FeMnSiCrNi alloys and the correlation between Mn-depleted zone, surface roughness and oxidation resistance. (October 2021) - da Cruz Passos, João Gabriel; Rabelo, Luís Fernando Pedrosa; de Freitas, Bruno Xavier; da Silva, Rodrigo; Della Rovere, Carlos Alberto; de Sousa Malafaia, Artur Mariano
Highlights: New Fe-17Mn-8Si-10Cr-4Ni-NbC alloy presented continuous mass loss in cyclic oxidation. Fe-17Mn-5Si and Fe-12Mn-5Si suffered anomalous behavior while Fe-17Mn-8Si did not. Fe-12Mn-5Si-9Cr-4Ni-NbC alloy exhibited internal oxidation forming iron oxides. Increasing Si content or decreasing Mn content reduced oxidation resistance. Metal-oxide interface roughness and CALPHAD data were related to alloys behavior. Abstract: Manganese and silicon effect on high-temperature cyclic oxidation was evaluated in three austenitic shape-memory FeMnSiCrNi alloys, including a novel high-silicon alloy (Fe-17Mn-8Si-10Cr-4Ni-NbC). Mass variation, Mn-depleted zone and metal/oxide interface roughness analyses were used to study the oxidation behavior. Renewed mass gain after spallation was observed for Fe12Mn5Si and Fe17Mn5Si alloys, while Fe17Mn8Si continuously lost mass, associated with low metal/oxide interface roughness and the ferritizing potential of Si. Low manganese availability led Fe12Mn5Si to suffer internal oxidation and iron oxide formation. Here, neither increasing silicon nor reducing manganese increased cyclic oxidation resistance of the alloys.